Exploring the biodiversity conservation potentials and eco-benefits of wetland corridors through sustainable ecotourism and landscape design approach - John Adekunle Adesina; Xiaolan Tang; Nnezi Uduma-Olugu (Ensaios de Geografia)
The primary goal of a green corridor is to efficiently connect ecosystems, providing animals with a readily accessible path between their habitats. Recently, the wetlands on the University of Lagos’s campus have experienced issues including flooding, deforestation, excessive sedimentation, obstructed streams, misuse, overuse, and wetland invasion. The green corridor behind the faculties of law and management science was chosen as a model supported by sustainability principles. It is an exemplary foundation for the university’s campus landscapes. The study aims to explore the potential for conserving biodiversity, the green open spaces eco-benefits, and the sustainable restoration strategies for wetlands. Direct survey techniques and qualitative data analysis were employed using the Strengths-Weaknesses-Opportunities-Threats (SWOT) matrix to analyze data obtained from primary sources. The study revealed threats to the wetlands, including habitat loss, overuse of resources, pollution, invasive species, disease, hunting, and climate change impacts. The study concludes that adaptive landscape planning, the design and construction of wetlands with physical features such as off-road bike lanes, nature walking trails, and raised hardwood platforms are ecologically sustainable and have low carbon emissions.